1987
DOI: 10.1038/bjc.1987.226
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two doses of adriamycin in the primary chemotherapy of disseminated breast carcinoma

Abstract: Summary Forty-eight patients with advanced breast carcinoma who had not received prior chemotherapy (minimum follow up 21 months) were randomised to receive either adriamycin 70 mgm 2 i.v. 3-weekly for 8 cycles (Regimen A) or adriamycin 35 mgm-2 i.v. 3-weekly for 16 courses (Regimen B). Objective responses were seen in 14/24 (58%) patients with regimen A (4 complete) and 6/24 (25%) with regimen B (1 complete) (P<0.02). The median duration of response was 14 months with regimen A and 6.5 months with regimen B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Only a few controlled prospective studies of the dose-response relationship in breast cancer have been published, and the results have not been consistent. A few studies have demonstrated a survival benefit from receiving a higher dose intensity (Carmo-Pereira et al, 1987;Tannock et al, 1988;Wood et al, 1994), while many controlled studies have failed to demonstrate any dose-response relationship (Hortobagyi et al, 1987a, b;Ludwig Breast Cancer Study Group, 1985;Walters et al, 1992;Fumoleau et al, 1993).…”
mentioning
confidence: 99%
“…Only a few controlled prospective studies of the dose-response relationship in breast cancer have been published, and the results have not been consistent. A few studies have demonstrated a survival benefit from receiving a higher dose intensity (Carmo-Pereira et al, 1987;Tannock et al, 1988;Wood et al, 1994), while many controlled studies have failed to demonstrate any dose-response relationship (Hortobagyi et al, 1987a, b;Ludwig Breast Cancer Study Group, 1985;Walters et al, 1992;Fumoleau et al, 1993).…”
mentioning
confidence: 99%
“…When the total dose of two regimes are equivalent, the dose intensity may be of critical importance as exemplified by the lower efficacy of 35 mg m-2 doxorubicin (q 3 weeks x 16) when compared to 70 mg m2 doxorubicin (q 3 weeks x 8) (Carmo-Pereira et al, 1987). In a randomised study comparing the effect of scheduling on treatment outcome, there was no difference bet*een the equi-dose intensive regimes of doxorubicin 25 mg M2 (weekly x 12) versus 75 mg m-2 (3 weekly x 4 (Richards et al, 1992).…”
mentioning
confidence: 99%
“…The objective response rates to doxorubicin are largely dose related. Low dose regimes (<60 mg m2 per 3 weeks) achieve a low response rate (approximately 30%) and a particularly low rate of complete remission (Gundersen et al, 1986;Carmo-Pereira et al, 1987;Gundersen et al, 1990;Jonsson et al, 1991). The response to conventional dose doxorubicin (60-70 mg m2 per 3 weeks) and to combination regimes containing doxorubicin are of the order of 50-60% (Carmo-Pereira et al, 1987;Steiner et al, 1983 and many others).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment was (Steiner et al, 1983) and is more effective at high (70 mg m2) than low (35 mg m2) doses (Carmo-Pereira et al, 1987). However, because anthracyclines are metabolised by the liver, elimination is delayed in patients with liver dysfunction (Benjamin et al, 1984).…”
Section: Methodsmentioning
confidence: 99%